Approach for colour homogenisation of chestnut (Castanea sativa [Mill.]) by thermal modification. (May 2014) - Correal-Mòdol, E.; Wimmer, T.; Huber, H.; Schnabel, T.
<x content-type="archive" xml:space="preserve">Abstract</x> Decay problems are responsible for undesirable discolouration of chestnut timber, which lead to a decrease in the value of the wood. As the use of coloured chestnut wood is mainly concentrated on energy fuel, the potential for the use of this coloured wood should be demonstrated. Reference without discolouration and coloured samples from various boards of chestnut wood from Catalonia in north–east Spain were used for the thermal modification at 200°C. The surface colour was determined according to the CIEL*a*b* system before and after the heat treatment as well as after exposure to UV-light. Furthermore, the mass loss, differential swelling and Brinell hardness of untreated and heat treated chestnut samples were also measured. Heat treating homogenises the colour of the reference and coloured chestnut samples and modifies the physical properties. The results of this study demonstrate the possibilities of coloured chestnut wood to develop new applications for it.